Presenting a Model of Factors Influencing the Development of Contemporary Sculptural Furniture with a Transdisciplinary Approach - Sanaz Pournaderi; Ahad Shahhoseini; Sajjad Pakzad; Meysam Khodashenas; Mustafa Bulat (هنرهای زیبا. هنرهای تجسمی)
In today's world, alongside fundamental human needs that have remained unchanged since the earliest human civilizations, a multitude of novel, complex, and multifaceted needs have emerged under various influences. These needs necessitate comprehensive, multidimensional, and integrated responses. Concurrently, the boundaries between different disciplines have become increasingly fluid and flexible, reflecting the multifaceted nature of contemporary society. Such needs cannot be fully addressed by traditional, single-discipline structures and boundaries. Employing an interdisciplinary approach and creating transdisciplinary products are among the most significant methods for innovatively solving complex contemporary challenges. In the present era, the boundaries between the art of sculpture and furniture design have been progressively blurred under various factors. These adjacent creative fields have exhibited increasing similarities in terms of design processes and techniques, production methods, materials, and the ultimate goals and functions of their products. In the contemporary era, sculptural furniture has emerged as a suitable solution to meet the complex and multifaceted needs of modern users. These pieces not only serve as functional products but also function as works of art. By merging the functional utility of furniture with the aesthetic and symbolic functions of sculpture, they cater to not only the physical but also the emotional and spiritual needs of users. This research aims to identify the factors contributing to the emergence and development of sculptural furniture in the contemporary era and to propose a model that can serve as a useful tool for designers and manufacturers of these products. Sculptural furniture can be described as a transdisciplinary product, the result of the integration of sculpture and furniture, which has emerged at the border of industrial design and sculptural art. Therefore, with a transdisciplinary approach, the main factor of development is the convergence of sculpture and furniture, and the factors of this convergence have been investigated as secondary factors. Cultural, economic factors, technological progress, architectural development, and new approaches (postmodern and modern art and design approaches) were identified as effective factors in the convergence of sculpture and furniture, as well as secondary factors in the development of sculptural furniture in the contemporary period. After identifying the factors, with the aim of better understanding each of the factors, the representative examples of sculptural furniture in the last 4 decades were categorized and analyzed based on the most effective factors identified. The present research is qualitative in terms of the type of applied research, descriptive-analytical nature (descriptive context oriented), and in terms of the type of data and data analysis. The method and tool of information collection is desk-based. This research is in the realm of design studies, in the realm of "research for design". The society and sample studied are sculptural furniture between 1985 and 2023. The sampling method of non-random research and images of design works were also collected digitally and online.